Common Cuckoo Nestling Adapts Its Begging Behavior to the Alarm Signaling System of a Host - Wang, Jiaojiao; Ma, Laikun; Chen, Xiangyang; Yang, Canchao (Frontiers in Ecology and Evolution, 2022)
Cuckoo nestlings thrive as avian brood parasites. To acquire sufficient food from the host parents, cuckoo nestlings generally make louder begging calls than host nestlings, but this may cause them to be more likely to attract the attention of predators. Studies have shown that nestlings would respond to the alarm calls of their parents by begging less, or crouching and remaining silent as an adaptation to reduce the risk of being heard by predators. Nevertheless, research is lacking on how parasite nestlings respond to alarm calls of their host parents. We studied the common cuckoo (Cuculus canorus) and one of the most common cuckoo host species, the oriental reed warbler (Acrocephaus orientalis), using a playback experiment in Yongnianwa National Wetland Park during the breeding seasons from June to July, 2020–2021. The begging behaviors of either cuckoo or host nestlings were quantified by playing back the alarm calls of host adults toward common cuckoo, sparrowhawk (Accipiter nisus), or oriental turtle doves (Streptopelia orientalis). Meanwhile, normal begging without playback, playback of the natural singing of host adults, and background noise were included as behavioral reference, non-threatening comparison, and playback control, respectively. The results showed that the cuckoo and host nestlings produced similar levels of begging with or without playback of natural singing and background noise; however, both types of nestlings inhibited their begging intensity after hearing the playback of alarm calls, although they did not respond differently to the various alarm call playbacks. This study therefore elucidated that coevolution has selected the common cuckoo nestlings that adapt their begging behavior to the parent–offspring communication of alarm signaling in their host, oriental reed warblers.